Desain Pendidikan Pembebasan Bagi Anak Berkebutuhan Khusus sebagai Jalan Humanisasi - Lourine Sience Joseph (Proceedings of The ICECRS, 2019)
Issues of Liberation Education for children with special needs (Heward), (Wiyani 2014: 2) become a n interesting phenomenon that requires educational innovation. the philosophy of ABK education innovation is liberation both physically and psychologically, as human beings. Bandhie Delphie (2012: 2) revealed that children with special needs have their own learning characteristics and specificities. Likewise, children with special needs at the Leleani PLB school and Pelita Kasih Ambon. They need a pattern of liberation education as a way of humanization. The purpose of this paper is to design liberation education to find patterns of education that free children with special needs. The implication is that every child will accept his existence as a free human being, an independent human being, especially a humanist person. The method used to collect and analyze problems based on research data is qualitative with a descriptive approach whose results are dialogue and communication with love and affection. Apart from that consientization (Freire, 1984: 41) self as a human being. The conclusion of liberation education through dialogue and communication in love and affection and the effort to build self-awareness of children with special needs is the design of liberation education for children with special needs as a way to discover the human nature of themselves as human beings.